Stunting Prevention Efforts by KKN 72 UINSA Through Parenting and Nutrition Workshop in Jeladri Village, Winongan District, Pasuruan Regency - Adibah, Niswah; Alfani, Mukhammad; Rahmadani, Dian Perdana Putri; Nurkholisa, Eka; Salsabila, Salsabila; Anisah, Sofiyatul; Lusiana, Nova (Jurnal Pengabdian Nusantara, 2024)
Based on the Indonesian Nutrition Status Survey (SSGI) in 2022, the prevalence of stunting in toddlers in Indonesia reached 21.6%. Meanwhile, the prevalence rate of stunting cases in 2024 Pasuruan district shows a percentage of 6.09%. A review of conditions in Jeladri Village shows that efforts to increase awareness of stunting prevention still need to be improved. This study aims to improve stunting prevention strategies based on education and workshops on parenting and nutrition in Jeladri village. The research method used in this research is descriptive qualitative research with a sample population of 50 families and using purposive sampling method who have children with high risk of stunting. The results obtained in the final evaluation can be said that participants have a good understanding of stunting prevention, parenting and nutrition. With a good understanding, it can significantly increase the value of community knowledge and have a positive impact on increasing community efforts to prevent stunting because with adequate knowledge the community tends to be able to take the right steps to prevent stunting from an early age.